Alkali metal modified iron‐nickel oxygen carrier to produce hydrogen‐rich synthesis gas by chemical looping gasification with pine sawdust. (23rd October 2020) - Wang, Pengcheng; Pu, Ge; Liu, Qiwen; Xiong, Weicheng
Summary: In the research of biomass chemical looping gasification technology, the production of hydrogen‐rich synthesis gas has received increasing attention. In this paper, iron‐nickel oxygen carriers were prepared by the mechanical and impregnation method. Chemical looping gasification experiments were performed with pine sawdust in a self‐built fixed‐bed reactor to prepare hydrogen‐rich synthesis gas. Experimental results showed that for the iron‐nickel oxygen carrier with a loading ratio of 3% NiO under reaction conditions of 800°C, ratio of steam content to biomass (S/B) of 1.25, and ratio of lattice oxygen to biomass (O/B) of 0.2, the volume fraction of hydrogen in the synthesized gas reached 43.06%; correspondingly, the carbon conversion rate was 78.22%, the low calorific value of syngas was 7.49 MJ/Nm 3, and the gas production rate was 1.25 Nm 3 /kg. After modification of the iron‐nickel oxygen carrier with a mass ratio of 5% K2 CO3, the volume fraction of hydrogen in the prepared synthesis gas increased to 47.83%, the corresponding carbon conversion rate was 85.44%, and the low‐level calorific value was 7.95 MJ/Nm 3 . The gas production rate was 1.49 Nm 3 /kg. Abstract : Alkali metal modified low‐load 3% NiO iron‐nickel‐oxygen carrier can prepare hydrogen‐rich synthesis gas with a volume concentration of 47%. The modification of alkali metal can strengthen the preparation of hydrogen‐rich synthesis gas, and the efficiency has decreased after 15 cycles. We found that it is because of the loss of alkali metal.